MOMENT – Management of Otitis Media with Effusion in Cleft Palate: protocol for a systematic review of the literature and identification of a core outcome set using a Delphi survey - Harman, N; Bruce, I; Callery, P; Tierney, S; Sharif, M; O’Brien, K; Williamson, P (BioMed Central, 2013)
Background Cleft palate (CP) has an incidence of approximately 1 in 700. Children with CP are also susceptible to otitis media with effusion (OME), with approximately 90% experiencing nontrivial OME. There are several approaches to the management of OME in children with CP. The Management of Otitis Media with Effusion in Children with Cleft Palate (MOMENT) study is a feasibility study that includes the development of a core outcome set for use in future trials of the management of OME in children with CP. Methods/Design The MOMENT study will include a systematic review of the literature to identify a list of outcomes that have previously been reported. This list of outcomes will be used in a Delphi study with cleft clinicians. The Delphi study is anticipated to include three rounds. The first round will ask clinicians to score the outcome list and to add any outcomes they think are relevant. The second round involves presentation of scores according to stakeholder group and the opportunity for participants to rescore outcomes. To ensure that the opinion of parents and children are sought, qualitative interviews will be completed with a purposive sample in parallel. In the final round of the Delphi process, participants will be shown the distribution of scores, for each outcome, for all stakeholder groups separately as well as a summary of the results concerning outcomes from the qualitative interviews with parents. A final consensus meeting will be held with all stakeholders, including parents and children, to review outcomes. Discussion A core outcome set represents the minimum that should be measured in a clinical trial for a particular condition. The MOMENT study will aim to identify a core outcome set that can be used in future trials of the management of OME, improving the consistency of research in this clinical area.